Klebsiella pneumoniae co-infection leads to fatal pneumonia in SARS-CoV-2-infected mice - Villalva, Crystal; Patil, Girish; Narayanan, Sai Sankara; Ghimire, Roshan; Chanda, Debarati; Samarakoon, Nishantha; Snider, Timothy; Ramachandran, Akhilesh; Channappanavar, Rudragouda; More, Sunil (Frontiers in Virology, 2024)
SARS-CoV-2 patients have been reported to have high rates of secondary Klebsiella pneumoniae infections. K. pneumoniae is a commensal that is typically found in the respiratory and gastrointestinal tracts. However, it can cause severe disease when a person’s immune system is compromised. Despite a high number of K. pneumoniae cases reported in SARS-CoV-2 patients, a co-infection animal model evaluating the pathogenesis is not available. In our cohort of COVID-19-positive human patients, 38% exhibited the presence of K. pneumoniae. Therefore we developed a mouse model to study the disease pathogenesis of SARS-CoV-2 and K. pneumoniae co-infection. BALB/cJ mice were inoculated with mouse-adapted SARS-CoV-2 followed by a challenge with K. pneumoniae. Mice were monitored for body weight change, clinical signs, and survival during infection. The bacterial load, viral titers, immune cell accumulation and phenotype, and histopathology were evaluated in the lungs. The co-infected mice showed severe clinical disease and a higher mortality rate within 48 h of K. pneumoniae administration. The co-infected mice had significantly elevated bacterial load in the lungs, however, viral loads were similar between co-infected and single-infected mice. Histopathology of co-infected mice showed severe bronchointerstitial pneumonia with copious intralesional bacteria. Flow cytometry analysis showed significantly higher numbers of neutrophils and macrophages in the lungs. Collectively, our results demonstrated that co-infection of SARS-CoV-2 with K. pneumoniae causes severe disease with increased mortality in mice.